2020
DOI: 10.3390/diagnostics10050336
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Zinc Levels in Males with Androgenetic Alopecia as Possible Predictors of the Subsequent Conservative Therapy’s Effectiveness

Abstract: Androgenic alopecia (AGA) is the most common type of progressive hair loss in man. The search for reliable predictors of the conservative treatment’s effectiveness is an urgent problem today. Forty-eight patients with AGA, stages I–IV by the Norwood–Hamilton scale, were treated for 4 months with 5% topical minoxidil joints with corrections for trace element and vitamin imbalances. In most cases, the positive therapy’s effect was shown in the parietal but not in the occipital area, whereas that effect was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Kondrakhina et al [29] reported that AGA in men with a serum zinc concentration of ≦65.4 μg/dL is more resistant to topical minoxidil and mineral correction than that in those whose serum zinc concentration was above the cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…Kondrakhina et al [29] reported that AGA in men with a serum zinc concentration of ≦65.4 μg/dL is more resistant to topical minoxidil and mineral correction than that in those whose serum zinc concentration was above the cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…However, a non-significant relationship was found between the grade of alopecia and zinc level. 36 Gowda involved other non-scarring hair loss problem like telogen effluvium and alopecia areata and detect for other micronutrients, nevertheless, zinc deficiency was seen in 11.76% of participants with MPHL, and no significant difference in other micronutrients was observed between micronutrient levels and androgenetic alopecia. 37…”
Section: Androgenic Alopeciamentioning
confidence: 97%
“…Kondrakhina et al 36 in his case-controlled study that enrolled males with androgenetic alopecia, studied many nutrient parameters, however, differences were shown in zinc content only. El Esway et al similarly tested males and demonstrated a similar outcome.…”
Section: Androgenic Alopeciamentioning
confidence: 99%
“…3 The process involves the transformation of terminal hair into vellus hair under the influence of both hormonal and genetic factors. 4 AGA can have psychosocial complications, including depression, low self-esteem altered self-image, and less frequent and enjoyable social engagements. In patients with AGA due to continuous disease progression, quality of life (QOL) gets impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Established links between androgens and MPHL has led to the term androgentic being used in reference of the condition 3 . The process involves the transformation of terminal hair into vellus hair under the influence of both hormonal and genetic factors 4 …”
Section: Introductionmentioning
confidence: 99%